An impact evaluation of the conditional cash transfers to education in praf: an experimental approach - Souza, Priscila Zeraik de (2005)
This paper uses data from a social experiment in Honduras to estimate the educational impact on children participating in PRAF II, a social program that has two components: demand-side intervention – conditional cash transfers to families whose children are attending school on a regular basis – and supply-side intervention - cash transfers to improve the quality of the schools. The results of the difference-in-differences and cross-sectional regressions indicate that the conditional cash transfers increase school attendance and reduce drop out rates; but they show no impact whatsoever from the supply-side intervention. The results of a Markov schooling transition model, used to assess the impact of the demand-side intervention, show that the program effectively facilitates progression through the grades. When we used a simulation method to evaluate the long-term impact of exposure to the program and a bootstrap method to test the statistical significance of our estimations, we found that if children were to participate in the program between the ages of 6 and 12, they would experience an improvement equivalent to 0.76 years in their average education level, and 35% more children would finish primary school. One notable result is that the conditional transfers have a significant impact on the poor, but have no impact on those who are not poor. Furthermore, the program was seen to reduce educational inequalities between rural and urban areas.